Relationship Between Blood Glucose Levels With Albumin and HDL (High-Density Lipoprotein) Levels In Diabetic Ulcers: Hubungan Kadar Glukosa Darah Terhadap Kadar Albumin dan Kadar Kolesterol HDL (High-Density Lipoprotein) Pada Pasien Ulkus Diabetikum - Ilmi, Isyfa'ul; Puspitasari, Puspitasari (Universitas Muhammadiyah Sidoarjo, 2023)
Diabetes mellitus is a disease caused by disorders of the body’s metabolism, because blood glucose levels have a increased or hyperglycemia. According to the IDF in 2021 DM sufferers have increased from 463 million people (9.3%) to 537 million people (10.5%) in 2021. The purpose of this study was to determine the relationship between blood glucose levels and blood albumin and HDL cholesterol in diabetic ulcer patients. The design of this study was a cross-sectional method, in 30 respondents with diabetes mellitus with diabetic ulcers who were undergoing treatment at the Sidoarjo Luka Home. Examination of glucose, albumin and HDL cholesterol was carried out using the enzymatic method using a photometer, on 28 May – 20 June 2022. The results of the study were analyzed using Pearson’s Parametric Correlation statistics. Blood glucose levels with blood albumin levels have a strong correlation with a negative correlation direction (r = -0.470 p= 0.009), while blood glucose levels with HDL (High-Density Lipoprotein) cholesterol levels have a weak correlation with a negative correlation direction (r=-0.375 p=0.041).